Tensions in Learner Support and Tutor Support in Tertiary Web-based English Education in China - Tong Wang (Athabasca University Press, 2006)
Based on the findings of a national survey conducted in 2004 designed to examine the support systems for both learners and tutors engaged in tertiary-level Web-based English education in mainland China, this paper reports the findings of secondary analysis by identifying the tensions in the current learner and tutor support systems. For learner support, four tensions were analyzed: (1) vigorous institutional learner support efforts versus learner utilization of the provisions; (2) learner qualities development versus academic support; (3) learner technical competence versus learner participation in online services; and (4) the relationship of face-to-face components and online components in learner support system design. For tutor support, four tensions were identified: (1) institutional conceptual understanding versus the actual practices; (2) tutor' enthusiasm versus tutor’s perception of online education; (3) tutor responsibilities versus tutor commitment, and (4) current tutor support service repertoire versus tutor improvement areas. The paper analyzes possible causes for the tensions and proposes some solutions to address these tensions.